Time to treatment failure following initiation of fingolimod versus teriflunomide for multiple sclerosis: a retrospective US claims study. (1st February 2020) - Vieira, Maria Cecilia; Conway, Devon; Cox, Gina Mavrikis; Peeples, Miranda; Bensimon, Arielle G.; Macheca, Monica; Herrera, Vivian
Abstract: Objective: Disease modifying therapies (DMTs) for multiple sclerosis (MS) aim to delay progression and reduce relapses. Evidence is limited on the comparative effectiveness of the oral DMTs fingolimod and teriflunomide. This study evaluated time to treatment failure among patients with MS who initiated fingolimod versus teriflunomide in real-world settings. Methods: The retrospective cohort included 18–64 year old patients diagnosed with MS who initiated fingolimod or teriflunomide during 12 September 2012 to 30 September 2015 within MarketScan Commercial and Medicare Claims. Patients were followed from treatment initiation (index date) until first treatment failure or censoring. Treatment failure was defined as the first occurrence of MS relapse (identified using a validated algorithm) or treatment discontinuation (≥60 day supply gap). Treatment failure was examined through Kaplan–Meier analysis and multivariable Cox regression adjusting for 1 year baseline factors (age, gender, plan type, region, index year, prior DMT use, baseline relapses, Charlson Comorbidity Index [CCI] and MS symptoms). Results: On average, patients treated with fingolimod ( n = 2704) were younger (43.6 versus 49.8 years) with lower CCI (0.4 versus 0.7) and more relapses at baseline (0.46 versus 0.42) than those treated with teriflunomide ( n = 1859). Median time to treatment failure was 19.5 months with fingolimod versus 9.6 months with teriflunomide ( p < .001). After controlling key demographic and clinical characteristics through multivariable regression, fingolimod was associated with 38.9% lower hazards of treatment failure versus teriflunomide (adjusted hazard ratio = 0.611; 95% CI: 0.559–0.669; p < .001). Conclusions: In a large cohort of US adults with MS, controlling for key baseline characteristics, fingolimod was associated with significantly longer time to treatment failure and lower risk of treatment failure compared with teriflunomide.